Analisis Tingkat Kepuasan Pengunjung terhadap Agrowisata Hidden Strawberry Garden di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng - QURO’, JAMIATUL; ARTINI, NI WAYAN PUTU; UTARI, NI KADEK SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Analysis the Satisfaction Level of Visitors to Agrotourism Hidden Strawberry Garden in Pancasari Village Sukasada District Buleleng Regency.  Visitor satisfaction is one of the important factors that support the development of agro-tourism, because its sustainability is determined by the satisfaction value of visitors who come to enjoy the tour. Agrotourism  Hidden Strawberry Garden  has complete facilities and unique tours that offer tours that explore the natural beauty of agriculture. The purpose of this research namely examine the characteristics, analyze the level of visitor satisfaction and analyze the level of suitability as an agro-tourism destination area of  Hidden Strawberry Garden . The data used is primary data by distributing questionnaires to 43 respondents. The analysis used is descriptive analysis,  Customer Satisfaction Index  (CSI), and  Importance Performance Analysis  (IPA). The results showed that visitors to agro-tourism  Hidden Strawberry Garden  dominated by women aged 17-25 years, last high school education, and work as students. The level of visitor satisfaction in visiting agro-tourism  Hidden Strawberry Garden  included in the satisfied category with a percentage of 73%. The average value of the level of conformity (TKi) level of importance and level of performance of all indicators consisting of several statement points is 90.03% so it can be concluded that the level of conformity in agro-tourism  Hidden Strawberry Garden  as a whole is in the category of "very suitable". Based on the level of suitability of agro-tourism  Hidden Strawberry Garden  has several things that need to be improved again in the position of quadrant I, namely garbage cans, parking lots, road access, communication networks, and directions.